Implikasi Putusan MK No.60/PUU-XXII/2024 terhadap Dinamika Partai Politik dan Calon Perseorangan (International Forum of Researchers and Lecturers, 2025)
Individual candidates are one of the nomination paths other than political parties that use public support as a prerequisite for being appointed as regional head candidates. Individual candidates are often referred to as democratic paths or grassroots paths because candidates who are successfully appointed truly come from public support that has been verified with certainty through factual verification. Individual candidates are also often seen as a solution to the high political dowries and the phenomena of corruption, collusion and nepotism that arise from the failure of political parties to carry out their function as the people's dignity. However, their existence has always been discredited by political parties, especially since the change in the nomination threshold by political parties which was decided in the Constitutional Court decision 60/PUU-XXII/2024. This literature study examines the potential presence of individual candidates in reducing political dowries and corruption which is also useful for upholding democracy with people's sovereignty. Therefore, it is necessary to consider reducing the threshold for support for individual candidates to balance the political battle of regional elections. By highlighting individual candidates as tough political opponents, it will trigger changes in the structure and working mechanisms of political parties in order to gain the sympathy of the people that has been lost over the past few decades